Acesso lexical: uma rota dupla para o português brasileiro - Medeiros, Joyse (2014)
The present study aims at verifying whether the way we access words is influenced by the lexicon structure of the language; more specifically, whether there is any difference in the way we recognize Brazilian Portuguese (BP) single and compound words. Two lexical decision tests were applied to eighty participants to determine (i) whether there are differences in mean reaction times and response accuracy between simple and compound words, and (ii) whether these differences correlate with the frequency of use of these words. Results of Experiment 1 provide evidence that there is a role for decomposition in the recognition of BP compounds. However, latencies of high frequency words in lexical decision tests 1 and 2 are consistent with predictions of full listing models. To explain these results we suggest a double route mechanism of lexical access, by which each word type will be more quickly accessed depending on its frequency and morphological properties.